Populist parties' popularity post power - Andreas Bergh; Anders Kärnä (Research Institute of Industrial Economics (IFN), 2024)
Populist parties have grown rapidly in popularity in most European countries, and are increasingly common in government coalitions. Analyzing 183 populist parties in 33 European countries from 1980 to 2021, we estimate the average effect of being in government on election results. On average, we find a post-power penalty at about 6 percentage points for populist parties lose about in the election after being part of the government. The size of the post-power penalty does not vary with growth, inequality, social spending, globalization, or unemployment during their term. Our results suggest that populist parties thrive when they can channel voters' negative sentiments without having the responsibility of governing.
Keywords: P16; 330; electoral competition; populism; political parties